(untitled) (International Conference on Education, Psychology and Humanities, 2026)
At present, in the field of education, special attention is being paid to the implementation and adoption of the STEM program, as well as to the use of open, flexible, individualized, and modern educational technologies. In accordance with the Resolution of the President of the Republic of Uzbekistan dated September 5, 2018, No. PQ–3931, titled “On Measures to Further Improve the Public Education System of the Republic of Uzbekistan for 2018–2021,” the tasks of improving the quality of education and introducing innovative educational technologies were defined. Based on this resolution, it is planned to gradually introduce and improve new state educational standards and general secondary education curricula, including the STEAM approach, relying on advanced international experience [1].